Sociabilidade e sentimento de insegurança urbana em pequenas cidades : o Norte do Paraná - Fernandes, Pedro Henrique Carnevalli (2012)
The comprehension of the human and social condition of life is indispensable to understand the geographical space formation and its changes. Within it is, among others the right of liberty and safety. The cities - or the urban space - known nowadays, understood as a cumulative result of a historical, political and cultural process, are the living space of the worldwide population, thus, became the main site of the achievement ties of sociability, and, consequently an unstable and complex field. The small cities, such as a focus, are part of the urban context. In the State of Paraná the presence of small cities is specially explained by the process of the sociospatial formation, it means, due to certain economic moments/cycles. In the case of Florestópolis and Nova Tebas, the county consolidation was stimulated by the coffee and cotton economy, respectively. After many factors from different levels, among them the declining of the main income sources, there was a declining of population in the county and loss of centrality in the urban core. This meaningful loss of goods and services, including insecurity, materializes in the contemporary reality of both cities. Therefore, there is a changing in the sociability among the inhabitants, reflex of a rarefied of the social relations, motivated by the capitalist system and by the globalization, and a real increase in the felling of urban insecurity, either by the growing cases of violence, by the influence of the means of communication or by the lack of public services which should guarantee safety in small cities. Starting from this point, the goals go on talking about this dynamic, mainly knowing the reality and the daily life of the inhabitants of Florestópolis and Nova Tebas.